Website Creation for Human Anatomy Using Macromedia Dreamweaver MX 2004 - author author (Jurnal Sistem Informasi, 2007)
Problems discussed in this paper is about the human skeleton information and explanations about the function and form the framework of the bones in the human body. The system framework is the motion on the human body as a result of cooperation between the bones to muscles. Bone as a passive motion would then arrange the framework of the system as a tool while the muscles active motion. The restrictions on the problem of the aforementioned problems in the writing of the authors limit this problem only on how the human skeleton anatomy website is designed for students who want to know the information the human skeleton with a scope that is taken from the data and anatomical information. The purpose of this scientific writing is creating a human skeleton anatomy website using Macromedia Dreamweaver MX 2004 This is to introduce the anatomy of the human skeleton to the general public especially the students through the Internet so students can know clearly about the human skeleton anatomical information.